Network-Aware Energy-Efficient Virtual Machine Management in Distributed Cloud Infrastructures with On-Site Photovoltaic Production - Camus, Benjamin; Dufossé, Fanny; Blavette, Anne; Quinson, Martin; Orgerie, Anne-Cécile (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Distributed Clouds are nowadays an essential component for providing Internet services to always more numerous connected devices. This growth leads the energy consumption of these distributed infrastructures to be a worrying environmental and economic concern. In order to reduce energy costs and carbon footprint, Cloud providers could resort to producing onsite renewable energy, with solar panels for instance. In this paper, we propose NEMESIS: a Network-aware Energy-efficient Management framework for distributEd cloudS Infrastructures with on-Site photovoltaic production. NEMESIS optimizes VM placement and balances VM migration and green energy consumption in Cloud infrastructure embedding geographically distributed data centers with on-site photovoltaic power supply. We use the Simgrid simulation toolbox to evaluate the energy efficiency of NEMESIS against state-of-the-art approaches.